Hybrid RSS-RTT Localization Scheme for Indoor Wireless Networks. (21st April 2010) - Bahillo Bahillo, A. A.; Mazuelas Mazuelas, S. S.; Lorenzo Lorenzo, R. M. R. M.; Fernández Fernández, P. P.; Prieto Prieto, J. J.; Durán Durán, R. J. R. J.; Abril Abril, E. J. E. J.
Abstract : Nowadays, a variety of information related to the distance between two wireless devices can be easily obtained. This paper presents a hybrid localization scheme that combines received signal strength (RSS) and round-trip time (RTT) information with the aim of improving the previous localization schemes. The hybrid localization scheme is based on an RSS ranging technique that uses RTT ranging estimates as constraints among other heuristic constraints. Once distances have been well estimated, the position of the mobile station (MS) to be located is estimated using a new robust least-squared multilateration (RLSM) technique that combines the RSS and RTT ranging estimates mitigating the negative effect of outliers. The hybrid localization scheme coupled with simulations and measurements demonstrates that it outperforms the conventional RSS-based and RTT-based localization schemes, without using either a tracking technique or a previous calibration stage of the environment.